REVITALIZING MSMES : AN EXAMINATION OF BUSINESS STRATEGY, INNOVATION AND ACCOUNTING INFORMATION SYSTEMS FOR IMPROVED PERFORMANCE - Ashsifa, Izza; Hidayanti, Alfiyani Nur; Mukhlisin, Ahmad (LPPM STIE Muhammadiah Bandung, 2023)
Micro, small, and medium enterprises (MSMEs) are essential for economic growth globally. However, they often face problems like unclear business plans, a lack of innovation, outdated accounting systems, and difficulty adapting to changes in the business world. These challenges lead to poor financial management and limited access to the right financial information. To overcome these problems, it’s important for MSMEs to create clear business strategies, encourage innovation, improve their accounting systems, and become more adaptable to changes. As a result, MSMEs will perform better and contribute more to the local economy. This study examines the effect of business strategy, innovation, and accounting information systems on MSME performance in Kudus Regency, using a sample of 391. The results showed that business strategy, innovation, and accounting information systems partially positively affected the MSME performance. Innovation, as a moderation variable, is able to strengthen the effect of business strategy on MSME performance. However, the results also show that accounting information systems have not been able to moderate the effect of business strategies on MSME performance. This research provides valuable insights for MSMEs, highlighting the importance of developing and executing suitable business strategies, promoting innovations, and establishing effective accounting information systems to improve performance.